Validation of Observation Sheets to Measure the Accuracy of Partograph Documentation - Erna Kusumawati; Intan Zainafree; Irwan Budiono (Universitas Muhammadiyah Semarang, 2025)
Background: Partographs are essential for monitoring labor progress, yet documentation is often incomplete or inaccurate, leading to delayed interventions and increased risks for mothers and newborns. However, there is currently no valid and reliable audit tool to evaluate the accuracy of partograph documentation. Objective: To develop and validate an audit tool for assessing the completeness and accuracy of partograph documentation. Methods: This study employed a Research and Development (R&D) design in four stages: (1) instrument development based on the 1994 WHO partograph template; (2) content validation by a panel of experts (obstetricians, senior midwives, and midwifery lecturers); (3) validity testing with 30 practicing midwives; and (4) reliability testing using Cronbach’s alpha. The instrument consisted of a 20-item checklist assessing documentation quality. Results: Expert review confirmed all items as valid. The validity test showed r-count values greater than the r-table (>0.361), and the reliability test yielded a high Cronbach’s alpha of 0.976, indicating excellent internal consistency. Conclusion: The developed audit tool is valid and reliable for evaluating the accuracy of partograph documentation. It can be applied in routine audits, quality control, and as an educational resource to strengthen healthcare workers’ competence in standardized, timely labor documentation.